Host–guest molecular doping guide for emissive organic semiconductor crystals. (27th October 2022) - Kuimov, Anatoly D.; Becker, Christina S.; Sonina, Alina A.; Kazantsev, Maxim S.
Abstract : Host–guest molecular compatibility criteria for the doping of conjugated highly emissive semiconductor crystals were revealed. Abstract : Molecular doping is an extremely useful approach for the optoelectronic properties tuning of organic materials, particularly crystalline luminescent semiconductors. Usually, dopant materials with good luminescence properties are used to improve the optoelectronic properties of host materials. However, the host-dopant compatibility and their selection criteria remain unclear. It is generally considered that the host and dopant should have a "similar" structure, which does not allow one to perform a thorough systematic design and choice of materials for obtaining low-defect doped organic semiconductors. Herein, we report a systematic experimental study coupled with existing literature data on host-dopant compatibility in a series of symmetric linear conjugated small molecules. Molecular planarity, short molecular axis and side polar substituents were demonstrated to be critical for successful host–guest molecular doping. Heterocyclic unit type and arrangement, molecular long axis, conjugation chain length and terminal substituents were demonstrated to not affect the host-dopant compatibility. An elaborated molecular doping guide is highly demanded for the systematic smart design of novel doped high-performance luminescent organic semiconductor materials.